EFFECT OF FEED RAW MATERIALS TYPES ON DISSOLVED PROTEIN CONTENT, PROTEIN HYDROLYSIS LEVEL AND FEED NUTRITION CONTENT OF ORANGE MANGROVE CRAB (Scylla olivacea) LARVAE FEED - Haryati, Haryati; Fujaya, Yushinta; Saade, Edison (Asian Journal of Aquatic Sciences, 2018)
Feed is one of the factors that affect the success of hatchery culture of mud crab (Scylla olivacea). The use of artificial feed in the form of microdiet can ensure availability, lower production costs and higher flexibility than natural feed. During this time the artificial feed used is a commercial feed, which is relatively expensive, therefore the need for research to produce artificial feed of good quality, with a cheap price.. The objective of this research is to determine the combination of raw material of artificial feed protein which produce dissolved protein content, protein hydrolysis degree and best protein content of feed. The experimental design used was completely randomized with eight treatments and three replications. The treatments were the use of various combinations of feed protein ingredients : A) 100% Artemia flour, B) 100% fish meal, C) 100% squid meal, D) 50% Artemia and 50% fish meals, E) 50% Artemia and 50% squid meals, F) 50% fish and 50% squid meals, G) 35% fish, 35% squid and 30% Artemia meals, H) commercial feed. The parameters used were dissolved protein content, protein hydrolysis degree and protein feed content. The results showed that the difference of feed protein raw materials had significant effect (p <0,05) on soluble protein content and feed protein hydrolysis degree. The highest content of soluble protein in in the diet with a protein raw material was squid meal, but not significantly different (P> 0,05) than Artemia meal and combination between 50% Artemia and 50% squid meals, but significantly different (P < 0.05) than other treatments. The highest degree of protein hydrolysis in the diet with a protein raw materials was Artemia meal, but not significantly different (P> 0.05) than in commercial feed as well as combination between Artemia and squid meal (P> 0.05), but significantly different (P <0, 05) compared to other treatments. Feed protein content according to the needs of mangrove crab larvae. Fat content with a protein raw materials was 100% artemia meal was higher than the need. Carbohydrate content with a protein raw materials were 100% artemia meal, a combination of 50% artemia meal and 50% squid meal and commercial feed according to the needs of mud crab larvae